A Jungian Archetypal Study of Main Characters in the TV Series Bridgerton Season 1 - Muslim, Ikhwan; Abdulloh, Abdulloh; Suprihandani, Eny; Nilda, Mutia (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study investigates the psychological development of the two main characters in Bridgerton Season 1—Daphne Bridgerton and Simon Basset—through the lens of Carl Gustav Jung’s archetype theory. The research is motivated by the need to understand how archetypal structures shape emotional growth, internal conflicts, and relational dynamics within popular screen narratives. The research employs a qualitative descriptive approach within the framework of literary criticism. Selected dialogues and narrative events were analyzed to identify the presence and function of five primary Jungian archetypes: Persona, Shadow, Anima/Animus, Hero, and Self. The analysis reveals that Daphne undergoes a transformation from conformity to societal expectations toward the assertion of a more authentic self. In contrast, Simon confronts his fragmented emotional identity by reconciling with his past, ultimately achieving greater psychological integration. These archetypal patterns illuminate each character’s individuation process and their evolving relationship dynamics. The findings suggest that Jungian archetypes not only serve as effective analytical tools for understanding character development in television narratives but also function as symbolic frameworks that resonate with audiences. By highlighting the interplay between psychological archetypes and narrative construction, this study contributes to broader discussions of how media representations provide insight into human emotional experiences.